Sedimenting Solidarity: Signs from the Madison Protest - (:unkn) unknown (My University, 2013)
The 2011 Wisconsin protest inspired the wide ranging production of handmade and commercially-produced signage. Five hundred signs were collected and preserved by the Wisconsin State Historical Society and others were obtained by the Smithsonian Museum of American History. Art historians and prominent art institutes have dismissed the aesthetic qualities of handmade signs, instead cataloging them as ephemeral historical artifacts. I argue that signs work similarly to other art forms in the modern era, such as advertisements and poster art, which have gained scholarly attention. This project uses the Madison protest as a case study in order to track the often wide and varied sedimentation of protest signs in the aftermath of social movements. While signs from Madison originally existed in the hands of protesters as communicative devices, they were also placed in storefront windows and home residences as symbolic reminders of solidarity. Other signs were placed in historical archives as artifacts of social discontent or (re)placed in museum spaces as conceptual works. The wide sedimentation of Wisconsin protest signs speaks to their versatility as functioning objects which worked as communicative devices using a language dependent on visibility, recycling, circulation, and community. It is important that the discipline of art history begin to recognize the worth of handmade signs as objects which archive the performative aspects of social movements as they continue to be created in moments of social resistance.
Keywords: Activist Art; Contemporary Art; Handmade; Protest Signs; Sedimentation; Social Movement Aesthetics